2008
DOI: 10.2196/jmir.1012
|View full text |Cite
|
Sign up to set email alerts
|

Answers to Questions Posed During Daily Patient Care Are More Likely to Be Answered by UpToDate Than PubMed

Abstract: BackgroundUpToDate and PubMed are popular sources for medical information. Data regarding the efficiency of PubMed and UpToDate in daily medical care are lacking.Objective The purpose of this observational study was to describe the percentage of answers retrieved by these information sources, comparing search results with regard to different medical topics and the time spent searching for an answer.Methods A total of 40 residents and 30 internists in internal medicine working in an academic medical center sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 16 publications
2
58
0
Order By: Relevance
“…For example, UpToDate was the preferred source in each domain, often by a large margin. Other studies have corroborated this finding with UpToDate frequently being the source most often used to generate the correct answer to various clinical questions [6,14,26]. What is difficult to glean from these results, however, is whether respondents actually prefer synthesized information generally or whether or not they are most familiar with and have ready access to UpToDate and responded accordingly.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, UpToDate was the preferred source in each domain, often by a large margin. Other studies have corroborated this finding with UpToDate frequently being the source most often used to generate the correct answer to various clinical questions [6,14,26]. What is difficult to glean from these results, however, is whether respondents actually prefer synthesized information generally or whether or not they are most familiar with and have ready access to UpToDate and responded accordingly.…”
Section: Discussionmentioning
confidence: 77%
“…However, despite the growing popularity of online resources, many barriers remain that prevent clinicians from frequently and successfully answering clinical questions using online knowledge searches. These barriers include, but are not limited to, time limitations, uncertain knowledge accuracy, technology malfunction, and knowledge seeker forgetfulness of the questions needing answered [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The average time for clinicians to look up clinical questions on PubMed ranges from 5 minutes to 60 minutes [7]. In addition, clinicians report high levels of dissatisfaction with their information seeking experience [8,9]. Ultimately, clinicians' challenges in consuming evidence from the primary literature may contribute to slowing the translation of scientific evidence [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 UpToDate is one of the most widely used computerized clinical knowledge management systems in the nation. 1,2,5,6 Previous studies of UpToDate and similar systems demonstrated that these systems improve acquisition of knowledge, increase the number of answered clinical questions, and change management decisions. 7,8 However, whether these changes lead to real improvements in clinical outcomes is unknown.…”
mentioning
confidence: 99%